Increased subcutaneous abdominal tissue norepinephrine levels in patients with anorexia nervosa: an in vivo microdialysis study - Nedvídková, J; Dostálová, I; Barták, V; Papezov, H; Pacák, K (Physiological research, 2004)
The present study was designed to measure interstitial levels of norepinephrine-regulating lipolysis (NE) in subcutaneous abdominal adipose tissue of anorexia nervosa (AN) patients and control subjects under basal conditions and after the local administration of an inhibitor of NE re-uptake, maprotiline. In vivo microdialysis technique was used to assess subcutaneous adipose NE levels in five women with AN (body mass index 14.62+/-0.47 kg/m(2)) and six age-matched controls (22.1+/-0.52 kg/m(2)). NE was assayed using high performance liquid chromatography with electrochemical detection after batch alumina extraction. Measured basal adipose tissue NE levels reflecting its interstitial levels were significantly increased in AN patients compared to the controls (106.0+/-20.9 vs. 40.0+/-5.0 pg/ml). The local maprotiline administration resulted in a significant increase in adipose tissue NE levels (AN patients: 440.0+/-28.6 vs. 202.0+/-33.0 pg/ml in the controls) in both groups. Markedly increased subcutaneous abdominal adipose tissue NE levels in AN patients compared to control subjects reflect increased sympathetic nervous system activity but not altered membrane noradrenergic transporter system in anorexia nervosa patients.
Keywords: mikrodialýza; břicho; dospělí; Analysis of Variance; Humans; Anorexia Nervosa; Norepinephrine; lidé; Female; noradrenalin; mentální anorexie; analýza rozptylu; subkutánní tkáň; Subcutaneous Tissue; Adult; Microdialysis; ženské pohlaví; Abdomen